Small Genres of Folklore in Lithuanian Folkloristics: The Legacy of Kazys Grigas - Zaikauskienė, Dalia (Tautosakos darbai, 2026)
Since the early days of Lithuanian folklore studies, small genres of folklore or so-called ‘minor folklore’ (smulkioji tautosaka), united by their brevity, have been considered a distinct type of folklore alongside folksongs and folk narratives. It is only in the 21st century, however, that small genres have been categorised as a form of oral folklore (sakytinė tautosaka). Professor Kazys Grigas is one of the few Lithuanian folklorists to have undertaken the task of describing and publishing them. Over time, he also established himself as Lithuania’s leading paremiologist. He did all the essential work necessary for researching proverbs and proverbial phrases, such as collecting, systematising and publishing them. Advocating historical-geographical and aesthetic methods, Grigas established a strong tradition of comparative proverb research in Lithuanian folkloristics. This article looks at the place of small genres in the wider system of Lithuanian folklore as it has developed over time in the context of Lithuanian folklore studies. It discusses the most significant research on small genres of folklore in Lithuania, with a particular focus on Grigas’ contributions to the field and his paremiological work.